1967
DOI: 10.1002/cber.19671000141
|View full text |Cite
|
Sign up to set email alerts
|

Halogenalkylhydroperoxide, II. Anlagerung von Halogen und Wasserstoffperoxid and Olefine

Abstract: Bei der Einwirkung von Brom bzw. Chlor und Wasserstoffperoxid auf Olefine in Dioxan bilden sich P-Brom-oder P-Chlor-alkylhydroperoxide. Die Reaktion wurde mit Methallylchlorid, Isobutylen, 2-Methyl-penten-(l), Tetramethylathylen und Cyclohexen durchgefiihrt.In der I. Mitteilung2) haben wir uber die Herstellung von P-Brom-alkylhydroperoxiden (1) durch Sauerstoffbehandlung von Olefinen in Gegenwart von Bromwasserstoff berichtet. Diese Reaktion verlauft entsprechend G1. (1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1967
1967
2000
2000

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…Thus, cleavage of the 2,3-carbon -carbon bond was the predominant reaction. This is the same type of reaction previously reported for the l-bromoand 1-cllloro-2-methyl-2-propyl hydroperoxides (4,5). It has been suggested (4, 5) that the cleavage proceeds via a four-atom cyclic peroxide.…”
Section: Reaction Of P-halol7ydroj1eroxides Wit12 Basesupporting
confidence: 81%
See 4 more Smart Citations
“…Thus, cleavage of the 2,3-carbon -carbon bond was the predominant reaction. This is the same type of reaction previously reported for the l-bromoand 1-cllloro-2-methyl-2-propyl hydroperoxides (4,5). It has been suggested (4, 5) that the cleavage proceeds via a four-atom cyclic peroxide.…”
Section: Reaction Of P-halol7ydroj1eroxides Wit12 Basesupporting
confidence: 81%
“…After work had begun there appeared several reports on the reactions of p-halo-and p-cyanohydroperoxides with base ( 4 6 ) . It is reported that l-chloro-2-methyl-2-propyl hydroperoxide is rapidly decoinposed by base to acetone and formaldehyde (4), while other workers report that upon treatment with base the brorno analogue, l-bromo-2-methyl-2-propyl hydroperoxide is converted partly to isobutylene oxide as well as to acetone and formaldehyde (5). A similar cleavage reaction was observed when 2-methyl-2-hydroperoxypropionitrile was treated with base (6).…”
Section: -Ohmentioning
confidence: 83%
See 3 more Smart Citations